PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 026 SIARANG-ARANG KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Miyatun '; Hendri Marhadi Hendri Marhadi; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract The research is about the low social studies students learning outcomes with an average 65,6. While the value of minimum of criteria of completeness is 67.  This researth is classroom action researth (CAR). That is suppose to increase the social studies students learning outcomes at fourth brrade of elementary school 026 Siarang-arang Pujud in Rokan Hilir District. Formulation of this research is: Does  the application of cooperative learning model type make a match can increase the learning outcomes of social studies at fourth grade of elementary school 026 Siarang-arang Pujud in Rokan Hilir district. The students learning outcomes before CAR is about 65,6% in fair category. Whereas after CAR in cycle 1 increase about 71,75% with fairly good category ard in cycle II is about 75% with good category the comparison of students  learning outcomes in before and after CAR in cycle I  inerease about 6,15% whereas from cycle 1 to cycle 2  incerease about 3,25% and from leased scare to cycle 1 increase about 61,15% and from based secore to cycle increase about 9,4%. The teacher is activity has an average incycle 1 is about 64,58%. Whereas in cycle 2 is about 83,33%. And the students activity have an average value in cycle 1 is about 60,41% and cycle 2 is about 79,16%. The result of this research is the  application of cooperative learning model type make a match can increase the social studies students learning outcomes at fourth brade of elementary school 026 Siarang-arang Pujud in Rokan Hilir District. Key word : Kooperative type make a match, The social student achievement